Degenerative changes of articular cartilage in association with mechanical stimuli - Kazuo Tanne (Elsevier, 2008)
This article was designed to review the association between degenerative changes of articular cartilage and mechanical stimuli. Finite element analysis revealed an induction of large compressive stresses in the anterior and lateral areas on the condyle by the maximum clenching and the prominent increases as the vertical discrepancy became greater. Increase of friction at the articular surface was indicated as a cause of larger stresses and the relevant disk displacement, which further induced an increase in stresses in the retrodiscal tissues, indicating the important role as a stress absorber. Increase in TMJ loading simulated by vertical discrepancy or excessive mouth opening produced a decrease in the thickness of cartilage layers, an increase in the numbers of clast cells and degenerative changes in the condylar cartilage associated with the expression of bone resorption-related factors. Excessive mechanical stimuli, irrespective of compressive or tensile one, induced HA fragmentation, expression of proinflammatory cytokines, an imbalance between matrix metalloproteinases and the tissue inhibitors, all of which are assumed to induce lower resistance to external stimuli and degenerative changes leading to bone and cartilage resorption. It is also revealed that various cytoskeletal changes induced by mechanical stimuli are transmitted through a stretch-activated or Ca2+ channel.